The Characteristics of Indonesian Language Digital Teaching Materials for Foreign Speakers with Culinary Content for Foreign Workers - Farinduani, Muhammad Dzakiy; Zulaeha, Ida; Nugroho, Yusro Edy (Universitas Negeri Semarang, 2023)
Teaching materials provided by the government for learning to foreign workers (tenaga kerja asing/TKA) are still limited, so it is necessary to have the characteristics of teaching materials that are adapted to the competencies needed by TKA. This research provided benefits for the scientific field of the Indonesian Language for Foreign Speakers (Bahasa Indonesia bagi Penutur Asing/BIPA), mainly BIPA learning theory especially for foreign workers, and could be a reference for other researchers to develop BIPA teaching materials for TKA. This study aimed to produce the characteristics of BIPA level A2 teaching materials in terms of listening skills with Indonesian culinary content aimed at foreign workers. This study used a Research and Development (R&D) research design. The characteristics of the teaching materials were compiled based on needs analysis data that had been conducted on nineteen foreign workers in four different companies. The characteristics of these teaching materials consisted of aspects of material/content, presentation, language, graphics, and Lectora applications. In the material/content aspect, there was the principle of completeness, the principle of conformity, the principle of convenience, and the principle of adequacy. In the presentation aspect, there were attractive, creative, and innovative principles, as well as systematic principles. The linguistic aspect included the principle of convenience, the principle of attractiveness, the principle of communication, and the principle of conformity. The graphic aspect included attractive, creative, and innovative principles. The aspect of the Lectora application included the principle of practicality and the principle of novelty.